The Effect of Word Square Method on the Arabic Learning Outcomes of Students MTs Assunniyyah Kencong Jember - Asni Furoidah; Zainuri Zainuri; Alaikin Nabiilah (UAS PRESS, 2026)
The influence of the Word Square method on Arabic learning outcomes can improve Arabic vocabulary mastery and student learning outcomes. This method can make the learning process more enjoyable and effective, so that students can more easily understand and memorize Arabic vocabulary. This study aims to determine the influence of the word square method on the Arabic learning outcomes of grade VII K MTs Assunniyyah Kencong Jember. The research method used was quantitative with a one-group pretest-posttest design on 26 students. The instrument was an Arabic vocabulary mastery test administered before and after treatment. The average pretest result was 63.23 and the average posttest increased to 72.76, with learning completeness increasing from 0% to 35%. The normality test analysis showed that the distribution of normal data (shapiro-wilk p > 0.05) and the paired samples t-test resulted in a value of p = 0.000 (< 0.05) with an average difference of -9.45 indicating a significant increase in learning outcomes after using the word square method. This method has also been proven to increase students' motivation, accuracy and involvement in learning Arabic.